Ecology and physical condition of red deer in the Iberian Peninsula: implications for management - Santos, João Pedro Valente e (2015)
The red deer (Cervus elaphus) is currently one of the most widespread and abundant wild ungulates in the Iberian Peninsula and is extremely important both ecologically, as a key species for the functioning of the ecosystems, and economically, as a major game species. In Iberia, red deer populations are subjected to different management systems that may affect the physical condition of the individuals, with further consequences for population dynamics. Studies investigating the effects of management practices and environmental conditions on the performance of red deer are still rare regarding Mediterranean ecosystems. Much of the knowledge concerning the ecology of red deer and the impact of management on its physical condition is based on studies conducted in northern and central regions of Europe, where climatological features and management practices differ from those observed in the Mediterranean areas of Iberia. Studies on a biogeographical scale can provide important insights into the relationships between species and a particular environment and contribute to the development of more targeted and appropriate management practices. The optimisation of sampling procedures and the fine-tuning of pre-existing analytical techniques are also fundamental to a more cost-effective monitoring and, therefore, are of enormous value to wildlife managers. In this context, the main aims of this thesis were: 1) to optimise the procedures used to assess the physical condition of red deer; and 2) to identify relevant management and environmental factors affecting the nutritional condition and stress physiology of red deer in the Mediterranean ecosystems of Iberia, as well as any potential interactions between those factors. Two studies with a methodological focus, presented in the first part of the thesis, demonstrated that the physical condition of red deer can be evaluated more simply, using more cost- and time-effective procedures than those traditionally used: i) it was shown that only one kidney and its associated fat is enough to assess nutritional condition in red deer; and ii) the feasibility of using near infrared spectroscopy to predict the concentrations of stress hormone metabolites was demonstrated using faeces of red deer for the first time. Subsequently, two large-scale observational studies, conducted in representative red deer populations found in Mediterranean Iberia, highlighted the importance of considering seasonal environmental variations and variables related to hunting management practices to better understand the nutritional and physiological ecology of red deer. High population densities had adverse effects on the nutritional condition of the deer and were associated with increased stress levels in natural populations without supplementary feeding. Massive hunting events involving the use of hounds were also identified as a potential source of chronic stress in red deer. The research presented in this thesis has clear implications regarding the management and monitoring of red deer populations in Mediterranean environments and is intended to help wildlife managers to implement more effective monitoring programmes and sustainable management practices.